Competition Commission vs South African Airways (2005) - Metton, Eulalie (Competition Commission case series., 2016)
In July 2005, the BA/Comair (Comair) executives were eagerly awaiting the Competition Tribunal's decision in the case brought by the Competition Commission against South African Airways (SAA). The case had been brought on behalf of the Nationwide Group, a domestic air travel rival to SAA. Nationwide lodged its complaint in October 2000, contending that, since 1999, SAA's incentives schemes to travel agents were so attractive as to force travel agents into selling SAA domestic travel tickets to the exclusion of Nationwide. This text examines how the Tribunal arrived at its verdict.